Adaptive Gamified Learning through Powtoon for Children with Special Needs’ Body Safety Awareness - Saifullah, Ahmad; Al Jinan, Ariqah Aulia Lu’lu; Ramadhani, Diya Fauziyah; Melati, Difa Rahma; Ibtisamah, Afidati Hilwa (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3676, 2025)
Children with special needs often face challenges in understanding abstract concepts such as body safety and personal boundaries. Traditional teaching approaches may not fully accommodate their diverse learning styles and cognitive abilities. This study aims to develop and evaluate an adaptive gamified learning model using Powtoon to enhance body safety awareness among children with special needs in elementary education. The research employed a developmental research design (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Participants consisted of teachers and students from a special education school. Data were collected through observation, interviews, and questionnaires, then analyzed descriptively to assess the feasibility, effectiveness, and engagement level of the Powtoon-based learning media. The findings indicate that the integration of gamification elements such as points, rewards, and interactive storytelling within Powtoon significantly increased students’ attention, motivation, and comprehension of body safety concepts. Teachers also reported that the media facilitated personalized learning, allowing instruction to adapt to each child’s pace and needs. In conclusion, the adaptive gamified learning model using Powtoon proved effective in promoting body safety awareness and supporting inclusive education. This study highlights the importance of leveraging digital technology to create accessible, engaging, and value-based learning experiences for children with special needs. The results contribute to the growing discourse on personalized and adaptive learning approaches that integrate technology for meaningful educational impact.